2008
DOI: 10.1057/jibs.2008.56
|View full text |Cite
|
Sign up to set email alerts
|

Beyond entry mode choice: Explaining the conversion of joint ventures into wholly owned subsidiaries in the People's Republic of China

Abstract: While there is a vast amount of research on firms’ choice of ownership form when entering a foreign market, little attention has been paid to changes in ownership forms of operation abroad after initial entry. Using transaction cost economics and institutional theory we identify a number of factors that may help to explain the likelihood of foreign firms’ converting their joint venture with a local firm into a wholly owned subsidiary. We formulate a number of hypotheses and test them against data collected thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(91 citation statements)
references
References 81 publications
(135 reference statements)
1
89
0
1
Order By: Relevance
“…Transaction costs broadly refer to the costs associated with doing business (Peng, 2014). Past studies have demonstrated that organisations are also more inclined to internalise activities that can be performed at lower cost whilst concurrently relying on the market for functional activities in which other organisations have a comparative advantage (Puck, Holtbrügge and Mohr, 2009;Klein, Frazier, and Roth, 1990). Such collaborations can pave the way for the parties to enjoy economies of scale, reduce cost and share risk (Hennart, 1988).…”
Section: Government Private Sector and Megaprojects: A Reviewmentioning
confidence: 99%
“…Transaction costs broadly refer to the costs associated with doing business (Peng, 2014). Past studies have demonstrated that organisations are also more inclined to internalise activities that can be performed at lower cost whilst concurrently relying on the market for functional activities in which other organisations have a comparative advantage (Puck, Holtbrügge and Mohr, 2009;Klein, Frazier, and Roth, 1990). Such collaborations can pave the way for the parties to enjoy economies of scale, reduce cost and share risk (Hennart, 1988).…”
Section: Government Private Sector and Megaprojects: A Reviewmentioning
confidence: 99%
“…Brouthers 2002;Brouthers and Hennart 2007;Hill, Hwang, and Kim 1990;Puck, Holtbrugge, and Mohr 2009) thus perpetuating a simplified view of the reality, in which smes typically enter foreign markets through exportbased modes. Such studies have taken into consideration the limits and constraints of smes going abroad, suggesting that such firms are less likely to pursue high-commitment forms of presence while preferring to approach foreign markets through direct or indirect exports (Gankema, Snuif, and Zwart 2000;Jansson and Sandberg 2008).…”
Section: Towards Developing a New Framework Of Smes' Escalation In Emmentioning
confidence: 99%
“…With more than US$95 billion in inward FDI in 2009(UNCTAD, 2011, during the time of data sampling, the country was one of the largest recipients of FDI globally. Moreover, according to the statistics of MOFCOM (2010) wholly-owned subsidiaries (WoS) and international joint ventures (IJVs) are the dominant ownership modes in China (Puck, Holtbrügge, & Mohr, 2009). Therefore, we focus on these two types of ownership modes in our analysis.…”
Section: Call the Bextent Of Control^and Thementioning
confidence: 99%
“…4 IJVs represent contractual relations in which two or more parent firms share ownership and control rights over the combined resources to accomplish goals they cannot accomplish on their own. WoS, on the other hand, represent contracts that grant the parent firm ownership and associated residual claim rights over the foreign subsidiary's assets and profits (Puck et al, 2009). Yan and Gray (2001b: 303) referred to an IJV as Bincomplete contract in which the partners have to live with substantial uncertainties down the road.^These factors suggest that WoS and IJVs may suffer from different types of agency conflicts.…”
Section: Hypotheses Developmentmentioning
confidence: 99%